Metanación de biogás en reactor de lecho fijo. Influencia de la configuración de la alimentación - Aragüés Aldea, Pablo; Gimeno Izquierdo, Chuan; Durán, Paúl; Mercader, Víctor Daniel; Francés, Eva; Peña, José Ángel; Herguido, Javier (Jornada de Jóvenes Investigadores del I3A, 2024)
This publication shows the experiments with a nickel-iron catalyst for the Sabatier reaction. The aim is to improve selectivities towards the desired product (methane) in a multiple-inlet reactor, in order to determine the optimal way to feed the reactants when carrying out the process.